Thermoregulation in premature infants: A mathematical model. (December 2016) - Pereira, Carina Barbosa; Heimann, Konrad; Czaplik, Michael; Blazek, Vladimir; Venema, Boudewijn; Leonhardt, Steffen
Abstract: Purpose: In 2010, approximately 14.9 million babies (11.1%) were born preterm. Because preterm infants suffer from an immature thermoregulatory system they have difficulty maintaining their core body temperature at a constant level. Therefore, it is essential to maintain their temperature at, ideally, around 37 °C. For this, mathematical models can provide detailed insight into heat transfer processes and body-environment interactions for clinical applications. Methods: A new multi-node mathematical model of the thermoregulatory system of newborn infants is presented. It comprises seven compartments, one spherical and six cylindrical, which represent the head, thorax, abdomen, arms and legs, respectively. The model is customizable, i.e. it meets individual characteristics of the neonate (e.g. gestational age, postnatal age, weight and length) which play an important role in heat transfer mechanisms. The model was validated during thermal neutrality and in a transient thermal environment. Results: During thermal neutrality the model accurately predicted skin and core temperatures. The difference in mean core temperature between measurements and simulations averaged 0.25±0.21 °C and that of skin temperature averaged 0.36±0.36 °C. During transient thermal conditions, our approach simulated the thermoregulatory dynamics/responses. Here, for all infants, the mean absolute error between core temperatures averaged 0.12±0.11 °C and that of skin temperatures hovered around 0.30 °C. Conclusions: The mathematical model appears able to predict core and skin temperatures during thermal neutrality and in case of a transient thermal conditions. Highlights: A new multi-node model of the thermoregulatory system of newborn infants is proposed. The model is customizable, i.e. it meets individual characteristics of the neonates. The model was able to accurately predict skin and core temperatures during thermal neutrality. This mathematical approach was capable of simulating thermoregulatory dynamics during thermal transients.